The Effect of Environmental Knowledge and Awareness on Green Behavior of BTN Syariah Employees in Medan City - Nurul Syahqilla; Muhammad Ramadhan; Atika Atika (LPPM UIKA Bogor, 2022)
This study aims to determine the effect of Environmental Knowledge and Awareness on the Green Behavior of BTN Syariah Employees in Medan City. This research is motivated because the level of paper use is increasing, followed by an increase in continuous cutting of trees which can lead to disasters in the future and have an impact on the continuity of the company's work. environment in each activity. The population in this study were all employees at BTN Syariah in Medan city with a total of 80 employees. And the number of samples is also 80 samples. This study uses a quantitative associative approach and data collection techniques using a questionnaire with a saturated sampling technique and analyzed using multiple linear regression methods. The results of this study partially show that all independent variables (Knowledge and Environmental Awareness) affect the Green Behavior of Employees. And simultaneously Knowledge and Environmental Awareness also affect the Green Behavior of Employees. It is concluded that all independent variables (Knowledge and Environmental Awareness) affect the Green Behavior of BTN Syariah Employees in Medan City